THE RESULTS OF THE EMBRYO TRANSFER TO HEIFERS FROM THE AYRSHIRE BREED - Constantin Nimbona; Nadezhda I Kulikova; Joseph Butore; Melance Ntunzwenimana (RUDN Journal of Agronomy and Animal Industries, 2019)
Dairy cattle’s breeding is an important industry, since it is providing milk and meat to population. Modern cows are significantly different from their ancestors in biology, behavior and in productivity. The scientific approach to feeding, condition of content and formation of focused heredity contributed to increasing the cows’ productivity. During the mammary gland formation and sexual cycles manifestation, puberty occurs, which makes it possible to obtain offspring and secretion of milk for feeding calves. The modern cows are capable of producing milk for their calves and for feeding people. The appearance of record cows, giving about 100 kg per day, and during lactation more than 32 tons of milk serves as an example for achieving such indicators of production. There are negative effects in reproduction biology, which takes place in modern cattle breeding. In order to breed highly productive cows, it is important to increase their livestock by intensive selection. Modernity is such that fertility is reduced due to cows’ reproductive functions inhibition. Modern practice shows that it is possible to introduce methods of obtaining several calves from one cow. It is generally accepted for this purpose use new reproduction methods, for example transplantation of embryos with high genetic potential. This technique is widely used in biotechnology of cows breeding. We have tested the method of preparing and conducting embryo transfer to heifers from 13 to 16 months old in the Kuban Agro-Association. The article presents indicators of heifer. It was revealed that not all animals reacted positively to superstimulation. Embryo transplantation showed that 35.1% of embryos survived after embryo transfer. Economic calculations have shown that for the rapid formation of a highly productive herd on the farm, it is advisable to use Ayrshire breed heifers capable of raising embryos and giving birth to healthy calves as recipients.